Activation of AMPK restricts coxsackievirus B3 replication by inhibiting lipid accumulation. (August 2015) - Xie, Wei; Wang, Lei; Dai, Qian; Yu, Hua; He, Xiaomei; Xiong, Junzhi; Sheng, Halei; Zhang, Di; Xin, Rong; Qi, Yajuan; Hu, Fuquan; Guo, Shaodong; et al.
Abstract: Coxsackievirus B3 (CVB3) is the major pathogen of human viral myocarditis. CVB3 has been found to manipulate and modify the cellular lipid metabolism for viral replication. The cellular AMP-activated protein kinase (AMPK) is a key regulator of multiple metabolic pathways, including lipid metabolism. Here we explore the potential roles AMPK plays in CVB3 infection. We found that AMPK is activated by the viral replication during CVB3 infection in Hela cells and primary myocardial cells. RNA interference mediated inhibition of AMPK could increase the CVB3 replication in cells, indicating that AMPK contributed to restricting the viral replication. Next, we showed that CVB3 replication could be inhibited by several different pharmacological AMPK activators including metformin, A769662 and AICAR. And the constitutively active AMPK mutant (CA-AMPK) could also inhibit the CVB3 replication. Furthermore, we found that CVB3 infection increased the cellular lipid levels and showed that the AMPK agonist AICAR both restricted CVB3 replication and reduced lipid accumulation through inhibiting the lipid synthesis associated gene expression. We further found that CVB3 infection would also induce AMPK activated in vivo . The AMPK agonist metformin, which has been widely used in diabetes therapy, could decrease the viral replication and further protect the mice from myocardial histological and functional changes in CVB3 induced myocarditis, and improve the survival rate of infected mice. Lastly, it was demonstrated that the AICAR-mediated restriction of viral replication could be rescued partially by exogenous palmitate, the first product of fatty acid biosynthesis, demonstrating that AMPK activation restricted CVB3 infection through its inhibition of lipid synthesis. Taken together, these data in the present study suggest a model in which AMPK is activated by CVB3 infection and restricts viral replication by inhibiting the cellular lipid accumulation, and inform a potential novel therapeutic strategy for CVB3-associated diseases. Highlights: AMPK is activated by the viral replication during CVB3 infection. Inhibition of AMPK by RNAi increases CVB3 replication. AMPK agonists restrict CVB3 replication through inhibiting the lipid accumulation. Metformin decreases the CVB3 replication in mice hearts. Metformin ameliorates functional changes in CVB3 induced myocarditis.